2009
DOI: 10.1021/jf902392a
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Dynamic TNO-Gastrointestinal Tract System with a Caco-2 Cell Culture Model: Application to the Assessment of Lycopene and α-Tocopherol Bioavailability from a Whole Food

Abstract: To exert their health effect, phytochemicals such as carotenoids and vitamin E have to be bioavailable. We investigated the digestive stability and intestinal absorption of lycopene and alpha-tocopherol from a whole food containing red tomatoes and sunflower oil using, for the first time, the dynamic gastrointestinal system TNO gastrointestinal tract model (TIM) coupled with Caco-2 cells. Digestive samples were added to Caco-2 cells after appropriate ultracentrifugation, filtration, and dilution. alpha-Tocophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…This model has shown its usefulness in studying the digestive stability of carotenoids from different food matrices throughout the gastrointestinal tract ). Combining the TIM system with Caco-2 cells, Deat et al (2009) found the potential applicability and predictive value of this in vitro approach to access the bioavailability of bioactive compounds from food or supplements.…”
Section: Micronutrient Bioavailabilitymentioning
confidence: 99%
“…This model has shown its usefulness in studying the digestive stability of carotenoids from different food matrices throughout the gastrointestinal tract ). Combining the TIM system with Caco-2 cells, Deat et al (2009) found the potential applicability and predictive value of this in vitro approach to access the bioavailability of bioactive compounds from food or supplements.…”
Section: Micronutrient Bioavailabilitymentioning
confidence: 99%
“…Since, the field has boomed with numerous IVD models, ranging from simple static mono-compartmental models to computer-controlled multi-compartmental dynamic IVD models, as reviewed by others (Glahn, Wien, VanCampen, & Miller, 1996;Guerra et al, 2012;Hur et al, 2011;McClements & Li, 2010;Payne et al, 2012;Yoo & Chen, 2006). Recent studies even raised the possibility of using human GI aspirates in IVD models (Ulleberg et al, 2011) or coupling IVD models with human cell cultures of Caco-2 epithelial cells or Caco-2 co-cultures with HT-29 mucus producing cells (Deat et al, 2009;Vors et al, 2012). Yet, the low accessibility and stability of human aspirates and the complexity of coupling IVD research with cell cultures, challenge the wide spread use of highly bio-relevant alternatives over simple protocols currently used in IVD models.…”
Section: Current Status Of Adult In Vitro Digestion (Ivd) Modelsmentioning
confidence: 99%
“…Yet, the low accessibility and stability of human aspirates and the complexity of coupling IVD research with cell cultures, challenge the wide spread use of highly bio-relevant alternatives over simple protocols currently used in IVD models. Further, in vitro cell culture systems have been coupled to some IVD models to enable investigating questions of cellular uptake and brush border enzymatic breakdown, which better elucidate the bioavailability of specific substances (Deat et al, 2009;Manione et al, 2015;Vors et al, 2012).…”
Section: Current Status Of Adult In Vitro Digestion (Ivd) Modelsmentioning
confidence: 99%
“…However, the use of a dialysis membrane to provide an absorptive surface does not model active cellular transport. To incorporate this function, it is possible to further analyze the digested fractions, after ultracentrifugation, filtration and dilution, and with a Caco-2 cell permeability assay (Deat et al, 2009). This model could be very relevant for the assessment of both the bioaccessibility and digestion of food-relevant NMs.…”
Section: In Vitro Non-cellular Fluid Modelsmentioning
confidence: 99%